Effect of in vitro simulated digestion on the anti-Helicobacter Pylori activity of different Propolis extracts - Paolo Governa; Giulia Romagnoli; Paola Albanese; Federico Rossi; Fabrizio Manetti; Marco Biagi (Taylor & Francis Group, 2023)
Helicobacter pylori (HP) is among the most common pathogens causing infection in humans worldwide. Oxidative stress and gastric inflammation are involved in the progression of HP-related gastric diseases, and they can be targeted by integrating conventional antibiotic treatment with polyphenol-enriched natural products. In this work, we characterised three different propolis extracts and evaluated their stability under in vitro simulated gastric digestion, compared to their main constituents alone. The extract with the highest stability to digestion (namely, the dark propolis extract, DPE) showed a minimum bactericidal concentration (MBC) lower than 1 mg/mL on HP strains with different virulence factors. Finally, since urease is one of the virulence factors contributing to the establishment of a microenvironment that promotes HP infection, we evaluated the possible inhibition of this enzyme by using molecular docking simulations and in vitro colorimetric assay, showing that galangin and pinocembrin may be involved in this activity.